Horizontal Gene Transfer and Population of Phyllosphere Bacteria on Transgenic and Nontransgenic Cotton - ROHANI CINTA BADIA GINTING; ANTONIUS SUWANTO; ARIS TJAHJOLEKSONO (Bogor Agricultural University, Indonesia, 2005)
The possibility of horizontal gene transfer of plant genomic DNA and bacteria in the soil, particularly as this relates to the possible transfer of genes encoding antibiotic resistance, has been seen as hazard associated with genetically engineered plants. It is hypothesized that introduction of bacterial genes into the plant genome leads to a higher probability of gene transfer from plants to bacteria due to the presence of homologous sequences. Bollgard (BG) cotton was constructed through the introduction of cry1A(c) gene, encodes for insecticidal activity againts Lepidopteran pests, together with genes for spectinomycin/streptomycin resistant (aad) and kanamycin resistant (nptII), into the genome of a conventional cotton variety, Delta Pine (DP). The aim of this study were to evaluate the ability of naturally competent Acinetobacter calcoaceticus strain ADP1 to take up and integrate transgenic plant DNA based on homologous recombination under optimized laboratory condition, and to compare phyllosphere microbial population resistant to antibiotic on leaves of transgenic and nontransgenic plant. The results showed that transformation of ADP1 cells with Bollgard DNA was not detected on nitrocellulose membrane nor in sterile soil. Total phyllosphere bacterial population on leaves collected from one month after planting were 1.3 x 108 and 1.6 x 108 cfu/g leave fresh weight for BG and DP, respectively. Samples collected after three month contained 5.9 x 107 and 7.1 x 107 cfu/g leave fresh weight for BG and DP, respectively. This study also showed that there was no significant difference of phyllosphere bacterial population resistant to streptomycin and kanamycin on leaves of BG or DP samples collected from one or three month after planting.